PENGGUNAAN SINGKATAN NAMA SEBAGAI MEREK KAITANNYA TERHADAP PENYELESAIAN SENGKETA KEPEMILIKAN MEREK SESUAI DENGAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Ade Irma Cendikia Hastami; Yudho Taruno Muryanto (Fakultas Hukum Universitas Sebelas Maret, 2025)
This article aims to describes and examines problems, first, to examine the use of name abbreviations as brands in Trademark Law No. 20/2016. Second, explain the types of the resolutions of brand ownership disputes. This type of research is normative legal research, which is prescriptive and use statutory research approach and case approach. The data used in this research are secondary data in the form of primary and secondary legal materials. Data collection techniques using library research. The data analysis technique used the deduction method. The results of this study show the regulation about the use of name abbreviations in a brand, in the Trademark Law. What kind of name abbreviations are prohibited so it can cause legal consequences for the brand registration. Then, regarding to the resolution of a brand ownership dispute the parties may use either a litigation or non-litigation (alternative dispute resolution) way that already state in Articles 83 to 93 of Law 20/2016. However, related to the use of name abbreviation of a country or national or international institution is specifically mention in Article 21 paragraph (2) letter b.